A Very Low-Calorie Ketogenic Diet Approach for Post-Bariatric Weight Regain: A Pilot Study - Ilaria Ernesti; Mikiko Watanabe; Alfredo Genco (J)
Weight regain (WR) after bariatric surgery, particularly sleeve gastrectomy, is a significant challenge, often driven by a combination of metabolic, behavioral, and lifestyle factors. Non-surgical interventions to manage WR are critical, given the increased risks and reduced efficacy of revisional surgeries. In this context, very low-calorie ketogenic diets (VLCKDs) have gained attention for their potential to promote weight loss and improve body composition in individuals struggling with WR. This study assessed the safety and efficacy of a VLCKD in 11 patients who experienced WR following sleeve gastrectomy. Over an 8-week period, patients demonstrated a significant average weight loss of 6.3% (p = 0.005), along with improvements in body composition, including reductions in body fat percentage (p = 0.003) and waist circumference (p = 0.003). Metabolic markers, such as insulin resistance (HOMA-IR), also improved significantly (p = 0.041). Although a decrease in the glomerular filtration rate was observed (p = 0.007), this finding is unlikely to be clinically relevant over the short term. Importantly, no major adverse events were reported, with only mild constipation observed. These results suggest that VLCKDs may be a promising non-surgical approach for managing WR post-bariatric surgery, though further studies are needed to assess long-term effects, especially on renal function.